Fidaxomicin reduces early toxin A and B production and sporulation inClostridium difficilein vitro. Issue 10 (October 2017) - Aldape, Michael J.; Packham, Aaron E.; Heeney, Dustin D.; Rice, Savannah N.; Bryant, Amy E.; Stevens, Dennis L.
Abstract : Purpose. : Fidaxomicin, a macrocyclic antibiotic, has been approved for the treatment of Clostridium difficile infection (CDI). Previous work by our group has demonstrated that some antibiotics at sub‐inhibitory concentrations stimulate early toxin production and sporulation by C. difficile. Prior studies revealed that fidaxomicin, when added to late stationary‐phase organisms, reduced exotoxin production and spore formation by C. difficile . However, the ability of fidaxomicin to trigger early virulence factor production and spore formation has never been investigated. Methodology. : Sub‐inhibitory concentrations of the RNA synthesis inhibitor fidaxomicin (1/4×, 1/8×, 1/16× MIC) were added immediately to lag‐phase cultures of historical (strain 9689) and epidemic BI/NAP1/027 (strain 5325) strains of C. difficile, and their effects on sporulation and toxin A (TcdA) and toxin B (TcdB) production were compared. Results/Key findings. : Even at sub‐inhibitory concentrations, all doses of fidaxomicin reduced both TcdA and TcdB gene expression and protein production in the historical and epidemic C. difficile strains. Fidaxomicin also dose‐dependently reduced viable spore production by the 9689 and 5325 strains. Reductions in spore formation were also observed in both strains treated with tigecycline and vancomycin. However, all concentrations of metronidazole stimulated a ˜2 log increase in spore production by the 5325 isolate. Conclusion. : The ability of fidaxomicin to suppress early exotoxin production and endospore formation by historical and epidemic strains of C. difficile may explain its clinical success in treating severe and recurrent cases of CDI disease.